Opportunities and Challenges of Enterprise Resource Planning (ERP) in Construction Companies in Indonesia: A Systematic Literature Review - Prasetya, Andika; Anshori, Mochammmad; Andriani, Nurita (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study delineates a systematic review of literature focusing on the opportunities and challenges associated with implementing Enterprise Resource Planning (ERP) in construction companies in Indonesia. Through the Systematic Literature Review (SLR) approach, this article evaluates and analyzes several related studies published within the last five years (2019-2023). This method allows the identification and synthesis of data from various sources such as academic journals, related publications, and databases, which are then analyzed to identify trends, opportunities, and challenges related to ERP implementation within the context of the construction industry in Indonesia. The findings from this literature review reveal a variety of benefits obtained by construction companies after adopting ERP systems, including improved operational efficiency, better resource management, and enhanced strategic decision-making. However, challenges also emerge, including issues related to adapting to change, integration with existing systems, as well as significant implementation costs and time. This analysis provides deep insights into the ERP implementation in the construction industry in Indonesia, providing a foundation for better understanding and further development in facing challenges and leveraging available opportunities.